The Impact Of Buyers’ Demography On Property Purchasing - Majid, Rohayu; Said,, Rosli; Daud, Md Nasir (Journal of Surveying, Construction and Property, 2017)
Demographic criteria usually relate to the person's characteristics. They measure people's affordability and capability, which could be at various levels. In addition, different demographies contribute differently to a buyer's choice in life. This study examines the impact of buyers’ demography on property purchasing using Chi-square Test. A questionnaire survey was used for collecting primary data in the state of Selangor with particular reference to buyers’ demography and housing attributes. The outcome shows that elements of the demography especially employment, marital status and gender have significantly affected property criteria which become main aspects that have always been considered by the buyer prior to purchasing a housing unit. Keywords: Property, Housing, Demography, Behaviour